Historical developments, hotspots, and trends in tardive dyskinesia research: a scientometric analysis of 54 years of publications - Baminiwatta, Anuradha; Correll, Christoph U. (Frontiers in Psychiatry, 2023)
Background Since being recognized as an important drug-induced clinical entity during the 1960s, tardive dyskinesia (TD) has generated an extensive body of research seeking to understand its clinical characteristics, epidemiology, pathophysiology and management. Modern scientometric approaches allow interactive visualization of large bodies of literature to identify trends and hotspots within knowledge domains. This study thus aimed to provide a comprehensive scientometric review of the TD literature. Methods Web of Science was searched for articles, reviews, editorials and letters with the term “tardive dyskinesia” in the title, abstract, or keywords through 12/31/2021. A total of 5,228 publications and 182,052 citations were included. Annual research output, prominent research areas, authors, affiliations and countries were summarized. VOSViewer and CiteSpace were used for bibliometric mapping and co-citation analysis. Structural and temporal metrics were used to identify key publications in the network. Results TD-related publications peaked in the 1990s, gradually declined after 2004, and showed a further small increase after 2015. The most prolific authors were Kane JM, Lieberman JA, and Jeste DV overall (1968–2021), and Zhang XY, Correll CU and Remington G in the last decade (2012–2021). The most prolific journal was the Journal of Clinical Psychiatry overall, and the Journal of Psychopharmacology in the last decade. Knowledge clusters in the 1960–1970s dealt with clinical and pharmacological characterization of TD. In the 1980s, epidemiology, clinical TD assessment, cognitive dysfunction and animal models predominated. During the 1990s, research diverged into pathophysiological studies, especially oxidative stress, and clinical trials on atypical antipsychotics, with a focus on clozapine and bipolar disorder. In the 1990–2000s, pharmacogenetics emerged. More recent clusters include serotonergic receptors, dopamine-supersensitivity psychosis, primary motor abnormalities of schizophrenia, epidemiology/meta-analyses, and advances in TD treatment, particularly vesicular monoamine transporter-2 inhibitors since 2017. Conclusion This scientometric review visualized the evolution of scientific knowledge on TD over more than five decades. These findings will be useful for researchers to find relevant literature when writing scientific articles, choosing appropriate journals, finding collaborators or mentors for research, and to understand the historical developments and emerging trends in TD research.